Disease progress of Peronosclerospora sorghi on some Ugandan maize genotypes - Bigirwa, G.; Adipala, E.; Esele, P.; Cardwell, K.F.; Okanya, S. (1997)
The type and level of disease reaction of Ugandan maize genotypes to Peronosclerospora sorghi was characterized using several variables during the second season of 1994 at two locations, Nazaretti in Mpigi district and Ikulwe in Iganga district. Maize genotypes differed significantly (p 0.05) in susceptibility as determined by the rate of disease increase (r), area under disease progress curve, and disease incidience.